Comparative study of three cultivars of jaboticaba berry: nutrient, antioxidant and volatile compounds - Xu, Shaosi; Pang, Yingying; Cai, Xiaoming; Chen, Qinchang; Jin, Gang; Zhang, Miao; Huang, Luqiang (Frontiers in Plant Science, 2023)
Jaboticaba is a tropical plant and its fruit rich in nutrients, volatile compounds, and biological activities, which considered to be an edible health benefits plant. Despite its popularity for fresh consumption, jaboticaba is rarely used in intensive processing in China. The content of nutrients and antioxidant in jaboticaba greatly impacts how it is processed healthy food. In this study, we evaluated the nutrients, antioxidant capacity and volatile compounds of three jaboticaba cultivars including Sabara, Argentina, and Fukuoka, respectively. Sabara had an abundance of volatile compounds, a suitable acid-sugar ratio, and a slightly lower antioxidant capacity, making it suitable for fresh consumption. Argentina is the richest in volatile compounds in ripe fruit, but slightly lighter in taste and acid-sugar ratio, making it suitable for dry products. The large size, juicy flesh, low acid-sugar ratio, and less volatile compounds content of Fukuoka also make it suitable for juice processing. The polyphenol content are relatively rich and antioxidant capacity in vitro showed fairly well in three cultivars berry. Three cultivars of jaboticaba berry exhibited different characteristics, providing reference evidences for the manufacturing and processing of jaboticaba health food.